2019
DOI: 10.1177/0897190019825915
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of High- Versus Moderate-Intensity Statin Therapy in Thai Patients With Acute Coronary Syndrome and Who Had Undergone Primary Percutaneous Coronary Intervention

Abstract: Although high-intensity statins are recommended for atherosclerotic cardiovascular disease, evidence has shown that Asians may need lower dose statins to achieve similar effect when compared to Caucasians. Moreover, awareness of adverse effects leads physicians to initiate moderate-intensity statins. Comparative of high versus moderate-intensive statins on LDL-C among patients who had undergone primary percutaneous coronary intervention (PPCI) for ST-segment elevation myocardial infarction (STEMI) are less est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Dyslipidemia is a major predictor for cardiovascular clinical outcomes after AMI (22). Recently, many studies have focused on a high-dose statin therapy to reduce the risk of cardiovascular death, Re-MI, and coronary revascularization in AMI patients (24)(25)(26), but not on the important roles of ACEIs or ARBs (4-7). It has been reported that circulating LDL-cholesterol/apolipoprotein B particles may be involved in promoting the upregulation of AT1 receptor genes and this leads to the structural overexpression of vascular AT1 receptors for angiotensin II in cultured vascular smooth muscle cells, as well as in hypercholesterolemic rabbits (13,27).…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is a major predictor for cardiovascular clinical outcomes after AMI (22). Recently, many studies have focused on a high-dose statin therapy to reduce the risk of cardiovascular death, Re-MI, and coronary revascularization in AMI patients (24)(25)(26), but not on the important roles of ACEIs or ARBs (4-7). It has been reported that circulating LDL-cholesterol/apolipoprotein B particles may be involved in promoting the upregulation of AT1 receptor genes and this leads to the structural overexpression of vascular AT1 receptors for angiotensin II in cultured vascular smooth muscle cells, as well as in hypercholesterolemic rabbits (13,27).…”
Section: Discussionmentioning
confidence: 99%